2015
DOI: 10.3168/jds.2014-9207
|View full text |Cite
|
Sign up to set email alerts
|

Postruminal synthesis modifies the odd- and branched-chain fatty acid profile from the duodenum to milk

Abstract: Milk odd- and branched-chain fatty acids (OBCFA) have been suggested as potential biomarkers for rumen function. The potential of milk OBCFA as a biomarker depends on whether their profile reflects the profile observed in the duodenum. The objective of this study was to evaluate whether the OBCFA profile in duodenum samples is reflected in plasma and milk. For this, 2 dairy cattle experiments were used. In experiment 1, 4 Holstein cows fitted with rumen and proximal duodenum cannulas were used in a 4×4 Latin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 38 publications
4
68
2
3
Order By: Relevance
“…For iso-C17:0, apparent transfer between duodenum and milk (on a g/d basis) was high (slope = 0.85), associated with a high intercept (1.80 g/d), whereas for anteiso-C17:0, the slope was greater than 1. This reflects that milk yield of these FA exceeds their duodenal flow, as previously reported by Vlaeminck et al (2006Vlaeminck et al ( , 2015, which may be attributed to either mobilization from adipose tissue or to synthesis of the 2 FA in the mammary gland. Mobilization of iso-C17:0 and anteiso-C17:0 from adipose tissue is probably of minor importance, because most of the trials included in that meta-analysis were designed with cows in mid-lactation when lipomobilization is negligible.…”
Section: Odd-and Branched-chain Fatty Acidssupporting
confidence: 76%
See 1 more Smart Citation
“…For iso-C17:0, apparent transfer between duodenum and milk (on a g/d basis) was high (slope = 0.85), associated with a high intercept (1.80 g/d), whereas for anteiso-C17:0, the slope was greater than 1. This reflects that milk yield of these FA exceeds their duodenal flow, as previously reported by Vlaeminck et al (2006Vlaeminck et al ( , 2015, which may be attributed to either mobilization from adipose tissue or to synthesis of the 2 FA in the mammary gland. Mobilization of iso-C17:0 and anteiso-C17:0 from adipose tissue is probably of minor importance, because most of the trials included in that meta-analysis were designed with cows in mid-lactation when lipomobilization is negligible.…”
Section: Odd-and Branched-chain Fatty Acidssupporting
confidence: 76%
“…However, the slopes of the models that represent apparent transfer efficiency from duodenal into milk were around 0.5 (when expressed on a yield basis for C15:0 and C17:0). This value is slightly lower than those reported by Vlaeminck et al (2015) that estimated the contribution of duodenal odd-chain FA to milk yield to be between 0.63 and 0.67. This indicates that part of the yield of these FA in milk arises from de novo mammary synthesis in line as reflected by the significant intercept of the model of milk C17:0 concentration (% of total FA) and the significant contribution of ruminal propionate to the secretion of C15:0 (Table 4).…”
Section: Odd-and Branched-chain Fatty Acidscontrasting
confidence: 72%
“…Studies with cultured human intestinal cells revealed the potential of branched-chain FA to be elongated by the action of this enzyme (Ran-Ressler et al, 2010). Based on daily milk secretion of anteiso C17:0, which exceeded its daily duodenum flow, we suggested the possibility of elongation of this branched-chain FA from anteiso C15:0 in animal tissues (Vlaeminck et al, 2015). Similarly, iso C15:0 elongation to iso C17:0 was suggested.…”
Section: Milk Fa or Their Ratios As Biomarkers Of Hyperketonemia: Phymentioning
confidence: 98%
“…Odd and branched chain fatty acids in milk are predominantly of microbial origin. Milk C15:0 and C17:0 are potential biomarkers of rumen function, as they are found in rumen bacterial lipids and may be partially synthesized endogenously from rumen substrates in the mammary gland (Fievez et al, 2012 andVlaeminck et al, 2015). The differences found between treatments (higher contents of these fatty acids in the milk of M goats) suggest an amylolytic rumen bacterial metabolism (Table 8).…”
Section: Milk Yield and Fatty Acid Profilementioning
confidence: 89%